Perspektif Remaja dan Pengasuh yang Hidup dengan HIV/AIDS terhadap Hambatan Pengungkapan Status HIV terkait Kepatuhan Pengobatan pada Masa Milenial - Rio Ady Erwansyah; Nursalam; Ninuk Dian K (Unram Medical Journal, 2022)
Disclosure of HIV status in children is part of comprehensive HIV management. Children must be informed about their illness diagnosis and explained if they must undergo long-term treatment. However, in the process, many obstacles are often encountered, such as stigma in the community that makes children reluctant to disclose their child's HIV status and the lack of experts who support the process. The stigma in the community also hinders adolescents in the process of adherence to treatment because of the fear related to discrimination and stigmatization that will be obtained. This systematic review was conducted through Scopus, Science Direct, and SAGE. The selection of inclusion criteria articles, articles published in the last five years and published in English, discussed the perspective of covering children's HIV status. Articles published not in English and articles with unclear literature except in this study. The PRISMA flowchart and JBI assessment checklist assessed bias and article quality. Twenty relevant articles will be reviewed. The results found that in caregiving and health workers should share responsibility and roles in diagnosis to support adolescents living on treatment and acceptance of their HIV status, empowering them to take responsibility for their health.